1966
DOI: 10.1149/1.2424029
|View full text |Cite
|
Sign up to set email alerts
|

Potential of a Platinum Electrode at Low Partial Pressure of Hydrogen and Oxygen

Abstract: A tight electrochemical system was constructed in which the PO2 above the cell solution was <10−9 atm. Comparing potentials with data from a previous paper (1) showed that very small amounts of O2 leaking into a closed system can have marked effects on potential behavior at low PH2 . Reduction of the oxygen leak to negligible proportions showed that: (a) the Nernst equilibrium relation for the H+/H2 couple holds only for PH2 in excess of 10−6 atm; (b) at low PH2 , trace amounts of O2, even in the presenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1

Year Published

1969
1969
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 4 publications
2
16
1
Order By: Relevance
“…From (5) it can be seen that for an equilibrium the Ela will decrease by 14.8 mV for a decrease in ao~ by a factor of 10. This is in opposition to what has been reported by several authors (Schuldiner et al, 1966;Jacob, 1971 ;Kjaergaard, 1976). However, the latter two refer to Schuldiner et al and obviously they have not calculated the value themselves.…”
Section: Theory Of Redox Potentialcontrasting
confidence: 65%
See 2 more Smart Citations
“…From (5) it can be seen that for an equilibrium the Ela will decrease by 14.8 mV for a decrease in ao~ by a factor of 10. This is in opposition to what has been reported by several authors (Schuldiner et al, 1966;Jacob, 1971 ;Kjaergaard, 1976). However, the latter two refer to Schuldiner et al and obviously they have not calculated the value themselves.…”
Section: Theory Of Redox Potentialcontrasting
confidence: 65%
“…However, they do not compare the measured Eh values with the concentration of dissolved oxygen to elucidate whether oxygen is the acting redox oxidant and water the reductant. Kantere (1972) and Balakireva et al (1974) did not compare the obtained results for Eh and dissolved oxygen (DO), neither did Jacob (1971), who refers to Schuldiner et al (1966). Wimpenny (1969) and Wimpenny and Necklen (1971) Although these calculations might be very defective, it is significant that the redox potential at lower DO-values decreases much more than that which can be calculated (1971) and Necklen (1971) and Necklen (1971) and Necklen (1971) and Necklen (1971) Jacob ( …”
Section: Redox Potential In Microbial Growth Systemsmentioning
confidence: 97%
See 1 more Smart Citation
“…The reason for this electrode performance is the low electron exchange density of oxygen at the platinum surface (Bockris & Huq 1970;Stumm & Morgan 1984). Only in pure water and with an extremely long response time, a linear relationship between the platinum electrode potential and the concentration of dissolved oxygen is measurable (Schuldiner et al 1966). Because of the slow kinetic of dissolved oxygen, mixed potentials from aerobic systems are dominated by traces of reductants rather than by the actual oxygen concentration.…”
Section: General Discussion and Conclusionmentioning
confidence: 99%
“…The dependence of ROP on pO" has been described by Squires and H osler [1958] and later by others [M atkovics et al, 1959;T engerdy, 1962;Lengyel and N y ir i, 1965;Marek et al, 1966], More recently, G rosz and F armer [1967] reported on the ROP of blood as a function of p 0 2. The electrochemical experiments by Schuldiner et al [1966] have shown that a positive correlation exists between pO., and ROP in the p 0 2 range of 1 to 10~9 atmospheres. A change in pO., of one order of magnitude causes a ROP change of about 60 mV.…”
Section: Introductionmentioning
confidence: 98%